Modular construction, magnetism and photocatalytic properties of two new metal-organic frameworks based on a semi-rigid tetracarboxylate ligand - Ling X.-Y.; Wang J.; Gong C.; Lu L.; Singh A.K.; Kumar A.; Sakiyama H.; Yang Q.; Liu J. (My University, 2025)
The solvothermal reactions of 5,5ˊ-(1,4-phenylenebis(methyleneoxy))diisophthalic acid (H4L) with cobalt(II) salts in presence of two N-donor ancillary ligands yielded two new metal–organic frameworks (MOFs) viz., [Co2(L)(bpz)(H2O)]n (bpz = 3,3′,5,5′-tetramethyl-4,4′-bipyrazole) (1) and [Co2(μ2-H2O)(H2L)2(tib)2·2CH3CN·2H2O]n (tib = 1,3,5-tris(1-imida-zolyl) benzene) (2). The single-crystal X-ray diffraction studies revealed that 1 displays 3,6-connected 3-periodic network with 2-fold interpenetration feature while 2 exhibits only 1D chain structure. The nature of ancillary ligands and the influence of N-donor ligands on coordination framework of these compounds have been discussed. The photocatalytic activities of these newly designed MOFs have been tested for the degradation of methyl violet (MV). The results of photocatalytic experiments demonstrated that both 1 and 2 displayed efficient photocatalytic performances to degrade MV under UV irradiation. The plausible mechanism through which both the MOFs displayed photocatalytic properties have been proposed through density of states (DOS) calculations. Also, the magnetic properties of both the MOFs have been analysed in detail which indicated χMT values of 6.02 and 6.54 cm3 K mol−1 for 1 and 2, respectively at 300 K which declined to 3.64 cm3 K mol−1 for 1 and 0.34 cm3 K mol−1 for 2 at 2 K. © 2019 Elsevier Inc.